MANAGEMENT OF FUNGAL POSTHARVEST DISEASES OF APPLE AND PEAR USING PLANT EXTRACTS - HASAN, AZHEN M.; MARZANI , QASIM A.; ABDULRAHMAN, DLEEN N. (Journal of Duhok University, 2022)
Economic losses, due to postharvest pathogens in markets and storages, are magnificent. Alternaria alternata and Penicillium expansum are considered the most important postharvest pathogens of apple and pear fruits. This work was aimed to investigate the principal pathogens on apple and pear fruits, the pathogenicity of the main pathogens, and assess of in vitro and in vivo efficacy of peel extracts of pomegranate, orange, and rutabaga against the main studied pathogens. The results of isolation designated A. alternata and P. expansum as major postharvest pathogens. The artificial inoculations of both pathogens resulted in the prominence of typical symptoms and the reisolation of the fungi proved Koch’s postulates. The results of in vitro assay revealed the highest inhibitory effect of rutabaga peel extract followed by orange peel extract while the pomegranate peel extract showed the least efficacy against both fungi. Another key fact that noticed is that both rutabaga and orange peel extract were most efficient against A. alternata than P. expansum. The results of in vivo assays have approved that pomegranate peel extract was the most effective plant extract against both pathogens of apple and pear fruits